The impact of expert visual guidance on trainee visual search strategy, visual attention and motor skills - Leff, Daniel R.; James, David R. C.; Orihuela-Espina, Felipe; Kwok, Ka-Wai; Sun, Loi Wah; Mylonas, George; Athanasiou, Thanos; Darzi, Ara W.; Yang, Guang-Zhong (Frontiers in Human Neuroscience, 2015)
Minimally invasive and robotic surgery changes the capacity for surgical mentors to guide their trainees with the control customary to open surgery. This neuroergonomic study aims to assess a “Collaborative Gaze Channel” (CGC); which detects trainer gaze-behaviour and displays the point of regard to the trainee. A randomised crossover study was conducted in which twenty subjects performed a simulated robotic surgical task necessitating collaboration either with verbal (control condition) or visual guidance with CGC (study condition). Trainee occipito-parietal (O-P) cortical function was assessed with optical topography (OT) and gaze-behaviour was evaluated using video-oculography. Performance during gaze-assistance was significantly superior [biopsy number: (mean ± SD): control=5·6±1·8 vs. CGC=6·6±2·0; p< 0.05] and was associated with significantly lower O-P cortical activity [∆HbO2 mMol x cm [median (IQR)] control = 2.5 (12.0) vs. CGC 0.63 (11.2), p < 0.001]. A random effect model confirmed the association between guidance mode and O-P excitation. Network cost and global efficiency and global efficiency were not significantly influenced by guidance mode. A gaze channel enhances performance, modulates visual search, and alleviates the burden in brain centres subserving visual attention and does not induce changes in the trainee's O-P functional network observable with the current OT technique. The results imply that through visual guidance, attentional resources may be liberated, potentially improving the capability trainees to attend to other safety critical events during the procedure.